The Influence of Competence and Work Motivation on Employee Performance - Ria Estiana; Deny Sudrajat; Sandi Nasrudin Wibowo; Imam Syafi'i (Quantitative Economics and Management Studies, 2022)
This study aims to find out whether there are problems regarding competence and work motivation on the performance of employees there. The population used is civil servants (PNS). Sampling in this study used a saturated sample, namely all civil servants (PNS) totaling 66 employees who will be studied using a data collection method using a questionnaire. The collected data is then processed using IBM SPSS 23 software. The data analysis technique uses instrument test, classical assumption test, multiple linear regression test. Hypothesis testing and the coefficient of determination. The results show that competence and work motivation simultaneously have a positive and significant effect on employee performance. However, there are still some indicators that need to be considered by the company from the variables of competence.